Immediate versus delayed insertion of the copper intrauterine device after medical abortion at 17–20 gestational weeks: a randomised controlled trial. Issue 1 (12th February 2021) - Constant, Deborah; Endler, Margit; Grossman, Daniel; Petro, Gregory; Patel, Malika
Abstract : Introduction: This trial reports on use of the copper intrauterine device (IUD) after immediate compared with delayed insertion following medical abortion at 17–20 gestational weeks (GW). Methods: This randomised controlled trial was conducted at one tertiary hospital and five community healthcare centres in Cape Town, South Africa. Eligible consenting women were randomised to immediate (within 24 hours) or delayed (3 weeks post-abortion) insertion of the copper IUD. Follow-up was at 6 weeks, 3 months and 6 months. Main outcomes were use of the original IUD and use of any IUD, including replacement IUDs at 6 weeks post-abortion. Secondary outcomes included rates of expulsion and malposition at 6 weeks, use of any IUD at 3 and 6 months, and acceptability of the IUD. Results: We recruited and randomised 114 women admitted for elective medical abortion between August 2018 and June 2019. In the immediate and delayed study arms, respectively, 45/55 (82%) and 12/57 (21%) women received the IUD as planned. By intention-to-treat, 56% in the immediate and 19% in the delayed arms were using the original IUD at 6 weeks (p<0.001), and 76% in the immediate and 40% in the delayed arms were using any IUD (p<0.001). Complete expulsion or removal occurred in 32% in the immediate and 7% in the delayed arms (p=0.044). Conclusions: Insertion of an IUD immediately after medical abortion at 17–20 GW results in increased use after 6 weeks compared with delayed insertion, however expulsion rates are higher than with interval insertion. Clinical trials registration: NCT03505047 ), Pan African Trials Registry (www.pactr.org), 201804003324963